The orphan's tale - Jenoff, Pam (Don Mills, Ontario, Canada : MIRA, 2017)
Sixteen-year-old Noa, forced to give up her baby fathered by a Nazi soldier, snatches a child from a boxcar containing Jewish infants bound for a concentration camp and takes refuge with a traveling circus, where Astrid, a Jewish aerialist, becomes her mentor.
Keywords: Circus -- Fiction; Teenage mothers -- Fiction; Jews -- Germany -- Fiction; World War, 1939-1945 -- Social aspects -- Fiction; Circus -- Fiction; Teenage mothers -- Fiction; Jews -- Germany -- Fiction; World War, 1939-1945 -- Social aspects -- Fiction; France -- History -- German occupation, 1940-1945 -- Fiction; France -- History -- 1940-1945, German occupation -- Fiction; Historical fiction; Historical fiction